Improving Student Teachers’ Digital Pedagogy through Meaningful Learning Activities (Malaysian Journal of Learning and Instruction, 2018)
Purpose â€“ This study aims to examine the attributes of meaningful learning that student teachers perceived as enabling them to improve their digital pedagogy. It is concerned with how the meaningful learning activities help to prepare student teachers to successfully integrate digital technologies in their future teaching practice.Methodology â€“ This study adopted a qualitative research design and was underpinned by a meaningful learning theory as the theoretical and analytical framework. A total of 24 final year student teachers participated in this study. Data were mainly collected through student teachersâ€™ reflections regarding their learning experience. Thematic analysis was utilized to analyze and present the findings.Findings â€“The findings offer some important insights into how the learning activities carried out in this Scholarship of Teaching and Learning (SoTL) project have directly and indirectly accelerated the acquisition of all the five attributes of meaningful learning. The findings of this study reveal that meaningful learning activities contribute to the improvement of the student teachersâ€™ knowledge of and skills in using Web 2.0. This improvement has boosted their confidence to integrate digital pedagogy in future teaching practices. The findings also indicate that although student teachers value their experiences in meaningful learning activities, they have some concerns regarding firstly, their capacities in applying digital pedagogy and secondly, the practicality of integrating Web 2.0 tools in the school setting because of several inherent limitations.Significance â€“ Meaningful learning activities when incorporated into teacher training programmes will expose student teachers to authentic experiences which will be beneficial for their own learning and future teaching practice.